2024
DOI: 10.3390/dj12010019
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Special-Care Dentistry among Dental Students at Universitas Indonesia: A Cross-Sectional Study

Atik Ramadhani,
Fiki Rizqa Izzati,
Diah Ayu Maharani
et al.

Abstract: Objective: To assess the perceptions of special-care dentistry (SCD) among dental students in the Faculty of Dentistry, Universitas Indonesia, Indonesia. Methods: This cross-sectional study used a self-administered online questionnaire, and all preclinical and clinical students were invited to participate. The survey items comprised four domains related to participants’ characteristics, perceptions of SCD, perceptions of managing patients with special needs, and perceptions of SCD education. The chi-square tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…A survey showed that 83% of students considered their undergraduate training on patients with "special needs" to be poor. When asked about their willingness to treat those people in the future, 50% were not willing to do so (24). Dentistry is considered a clinical field, and acquiring sufficient skills and receiving appropriate training is crucial, especially in the field of dental considerations of systemic diseases, as this can improve the level of oral and dental health of patients with systemic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A survey showed that 83% of students considered their undergraduate training on patients with "special needs" to be poor. When asked about their willingness to treat those people in the future, 50% were not willing to do so (24). Dentistry is considered a clinical field, and acquiring sufficient skills and receiving appropriate training is crucial, especially in the field of dental considerations of systemic diseases, as this can improve the level of oral and dental health of patients with systemic diseases.…”
Section: Discussionmentioning
confidence: 99%